2020
DOI: 10.1111/cdev.13379
|View full text |Cite
|
Sign up to set email alerts
|

Positive Shyness in the Brain: Frontal Electroencephalogram Alpha Asymmetry and Delta–Beta Correlation in Children

Abstract: Positive shyness is thought to be an approach‐dominant form of shyness, whereas non‐positive shyness is thought to be an avoidance‐dominant form of shyness. This study examined electrocortical and behavioral correlates of motivation and emotion in relation to these shy subtypes in 67 children (Mage = 10.41 years, SD = 3.23). Using resting state electroencephalography, findings revealed that positive shy and low shy children had greater relative left frontal alpha asymmetry compared to non‐positive shy children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 79 publications
(197 reference statements)
1
15
2
Order By: Relevance
“…For example, greater relative right frontal EEG activity has been consistently linked to increased risk for developing internalizing difficulties (Baehr et al, 1998;Bell et al, 1998;Blackhart et al, 2006;Diego et al, 2001;Gotlib, 1998;Henriques & Davidson, 1990, 1991Smit et al, 2007) and emotion dysregulation (Hannesdóttir et al, 2010). Although shy individuals do appear to experience these physiological vulnerabilities more readily than nonshy individuals (Fox et al, 1995;Poole et al, 2019;Poole & Schmidt, 2020b;Schmidt, 1999;Sutton & Davidson, 1997), impor-tantly, our results demonstrate that attentional-level factors may function to modify this risk.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…For example, greater relative right frontal EEG activity has been consistently linked to increased risk for developing internalizing difficulties (Baehr et al, 1998;Bell et al, 1998;Blackhart et al, 2006;Diego et al, 2001;Gotlib, 1998;Henriques & Davidson, 1990, 1991Smit et al, 2007) and emotion dysregulation (Hannesdóttir et al, 2010). Although shy individuals do appear to experience these physiological vulnerabilities more readily than nonshy individuals (Fox et al, 1995;Poole et al, 2019;Poole & Schmidt, 2020b;Schmidt, 1999;Sutton & Davidson, 1997), impor-tantly, our results demonstrate that attentional-level factors may function to modify this risk.…”
Section: Discussionmentioning
confidence: 60%
“…It is now widely accepted that individuals with dispositions characterized by shyness have an underlying physiology that distinguishes them from nonshy individuals on several different levels, including greater relative right frontal brain activity at rest (Fox et al, 1995;Poole et al, 2019;Poole & Schmidt, 2020b;Schmidt, 1999;Sutton & Davidson, 1997), higher and more stable heart rates (Kagan et al, 1988;Schmidt & Fox, 1994) and higher basal cortisol levels (Kagan et al, 1988;Schmidt et al, 1997). These distinct physiological correlates observed among shy individuals may be appropriately conceptualized as vulnerabilities because they are largely associated with, and predictive of, psychological maladjustment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, shyness and SAD may differ qualitatively (Heiser et al, 2003;Poole et al, 2017). Additionally, Poole and Schmidt (2020) found that positive shy children had a higher frontal positive deltabeta correlation than non-positive shy and low-shy children. The present study did not classify shyness and referred to general conceptual shyness which may be the reason for the inconsistent result.…”
Section: Discussionmentioning
confidence: 95%
“…That is, displays of extreme fear, anger, or sadness in context that pull for moderate levels of wariness or displays of negative affect in positive‐affect‐eliciting episodes. A view of higher delta‐beta coupling as supporting context‐inconsistent displays may also help to explain associations between positive shyness and increased delta‐beta coupling when positive shyness is measured during a speech task, for which negative affect is the dominant display (Poole & Schmidt, 2020). Subsequent work should continue to keep this possibility in mind and work to clarify the nature of this association.…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, most work on delta‐beta coupling is derived from studies that partition groups based on mean split (e.g., Najjar & Brooker, 2017; Phelps, Brooker & Buss, 2016; Poole & Schmidt, 2020), median split (e.g., Miskovic & Schmidt, 2009; Putman, 2011; Putman et al., 2012) or clinical classifications (e.g., Harrewijn et al., 2018; Miskovic et al., 2011). While this approach has been useful, it also has limitations.…”
Section: Introductionmentioning
confidence: 99%